Akhunjon Safarov’s Book of Poems "Sweet Spring" - qizi, Eshankulova Malika Zayniddin (European Journal of Life Safety and Stability (2660-9630), 2022)
The article describes the life of Akhunjon Safarov, his indelible mark in children’s literature, the uniqueness of the only book of poetry and, most importantly, the mastery of simple and fluent poetry in the "international language" that is easy for children to understand. It is said that it was written with. Opinions were expressed on how important teacher poems are in children’s understanding of folklore.